A study of natural radioactivity in thermal springs in Greece using gamma and alpha spectrometry - Petropoulou Kynigopoulou, Ilianna; Gelatsoras, Foivos; Siltzovalis, Georgios; Lagaki, Varvara; Madesis, Ioannis; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2025)
Thermal springs have a geographical distribution that is mostly shaped by major tectonic phenomena, such as volcanic events and extended fault zones. Thermal springs are known to exhibit elevated activities of natural radioisotopes, such as 226Ra and 222Rn. The present work aims to study the natural radioactivity in a few thermal springs in the Hellenic region. Seven water samples were collected from thermal springs in Therma and Nigrita of Serres, Kos Island, and around the perimeter and underwater of the volcanic peninsula of Methana. After preparation, the samples were measured with a calibrated, high-resolution HPGe spectrometer at the National and Kapodistrian University of Athens. Specific activities of natural radioisotopes of the 238U and 232Th series, as well as of 40K were deduced. The same samples were also measured with a factory-calibrated radon spectrometer RAD7 aiming at investigating the correlation of the specific activities obtained by alpha spectroscopy with those deduced by gamma-ray spectroscopy. The results show that such a correlation is clear. In addition, the results extracted with gamma-ray spectroscopy agree well with the values of activities measured in thermal springs, as found in international literature. Further investigation of the correlation between the alpha and gamma spectroscopy in additional water samples, as well as other types of matrices is underway.